PENENTUAN KADAR FLAVONOID TOTAL PADA EKSTRAK ETANOL DAUN ANDONG MERAH DAN DAUN ANDONG HIJAU - Dian Kartikasari; Adhisty Kharisma Justicia; Paula Endang (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Determination of flavonoid content in the ethanol extract of red andong leaves and green andong leaves, which was determined by the colorimetric method using Uv-Vis spectrophotometry, aims to determine the flavonoid levels in the ethanolic extract of red andong leaves and green andong leaves. nm, the total flavonoid content is calculated by linear regression equation y = 0.00757x + 0.0324 with the coefficient of relation rÂ² = 0.997842544. Determination of total flavonoid content was carried out by spectrophotometry based on the ability of flavonoids to form complexes with AlCl3. The flavonoid content obtained from the ethanol extract of red andong leaves is 0.329% and green andong ethanol extract is 0.4354%.